Local advancement flap: A case report - Syarief Makka; Hendro Sunjaya; Eky Nasuri; Vera Julia (Journal of Dentomaxillofacial Science, 2021)
Objective: A local flap, including an advancement flap, is useful for covering large skin defects on the head and neck. The incision of the advancement flap is carefully made to cover the main defect as efficiently as possible. Methods: A 34 years old female patient was referred to Department of Oral and Maxillofacial Surgery, Cipto Mangunkusumo National Central General Hospital and had a mandibular resection, extraction of tooth 45, and left condyle disarticulation, followed by fistulectomy, debridement, and squesterectomy. For closing the defect, a local advancement flap was made, the flap was incised, reduced, and pulled to wraparound the main site of the defect. Result: The local advancement flap combined with Burrow’s triangle design, result in complete closure of the defect and also has a maximum cosmetic appearance. Conclusion: Unipedicle-pedicle advancement flaps involve advancement by taking benefit of the skin elasticity, the advancement flap is also done by making an incision of the Burrow-triangles design subsequently bringing the skin laterally to level the length of the flap and the adjacent wound margin.